HOW CUSTOMER SATISFACTION MEDIATED BENEFITS OFFERED AND E-SERVICE QUALITY TO CUSTOMER TRUST AND REPEAT USAGE OF BSI MOBILE BANKING - Latri, Dwi Wahyuning; Solekah, Nihayatu Aslamatis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aimed to determine the relationship between customer satisfaction as a mediating variable and the benefits offered and e-service quality on customer trust and repeated use of BSI mobile users in Malang City. Purposive sampling was used in this study using a sample of 250 participants. Data analysis checks using a statistical model utilizing the SmartPLS 4 program for the structural-partial least square (SEM-PLS) model. The results of this study indicate that benefits offered and e-service quality directly affect customer satisfaction. Benefits offered, e-service quality, and customer satisfaction directly affect customer trust. E-service quality, customer satisfaction, and customer trust directly affect repeat usage. Benefits offered indirectly affect customer trust through customer satisfaction. E-service quality indirectly affects customer trust through customer satisfaction. E-service quality indirectly affects repeat usage through customer satisfaction .  All the results are accepted in direct and indirect testing. From this analysis, it can be inferred that Bank Syariah Indonesia clients in Malang tend to have high levels of satisfaction and trust in the quality of service at BSI Mobile as well as the ease and security of the services offered.